THE IMPACT OF EDUCATION ON QUALITY OF LIFE IN UZBEKISTAN - Xakim Murtazaqulovich Xudoyberdiyev (European Science Publishing, 2024)
This article examines the pivotal role of education in enhancing the quality of life in Uzbekistan, considering both its economic and non-economic dimensions. It explores how educational attainment correlates with employment rates, income levels, digital literacy, and social inclusion. Utilizing statistical data from Uzbekistan's State Statistics Committee and international organizations, the study employs regression analysis and surveys to highlight the impact of education reforms. Key findings reveal that higher education significantly reduces unemployment and increases income, with tertiary-educated individuals earning nearly double compared to those with secondary education. Additionally, education improves access to digital resources and civic engagement, although regional disparities and a digital divide remain pressing challenges. The article emphasizes policy recommendations, such as improving rural educational infrastructure, expanding access to online learning, and integrating vocational training. These measures aim to address existing inequalities and align educational outcomes with the demands of a rapidly evolving labor market.
Keywords: Education, quality of life, Uzbekistan, unemployment, income, digital literacy, regional disparities, educational reforms.